The Implementation of Balance Scorecard and Its Impact on Performance: Case of Universiti Utara Malaysia - Anuforo, Peter U.; Ayoup, Hazeline; Mustapha, Umar Aliyu; Abubakar, Ahmad Haruna (International Journal of Accounting & Finance Review, 2019)
The intensity of competition among contemporary Higher Education Institution (HEIs) has led to many of such institutions to focus more on how to provide high quality education so as to attain a suitable position in the university world ranking by adopting a suitable performance management. This study aims to demonstrate how UUM implement and uses the BSC to enhance and improve its strategic plans by addressing the issues facing its strategic management process. This study employed a qualitative case study approach. Data were collected using interview and reviewing the university quarterly and annual reports, organizational structure and the university’s webpage as well as its news bulletins. Data were analyzed qualitatively using thematic analysis. Consistent with Kaplan and Norton BSC model in public sector, findings indicates that the case institution implements the BSC ideology by adapting the concept such that it reflects the unique contextual needs of UUM. This study found that in implementing the BSC project, the university staff’s buy-in, top management commitment, organizational culture and communication strategy has significant effects on the case institution’s performance. Also, findings revealed that the implementation of BSC ideology in UUM has a significant impact on its performance in that it helps in improving the case institution’s overall university rankings. The implication of BSC implementation in UUM is that it helps the university management to monitor its performance with regard to its 2016-2020 phase II strategy plans. Future study should consider more institution that implements BSC so as to get more detail results that may be generalized.